An unusual cause of chronic abdominal pain after laparoscopic Roux en Y gastric bypass: Case report of a penetrating fish bone causing adhesions at the biliary-digestive junction resulting in partial obstruction and chronic symptoms. (2016) - Ochieng, Vincent; Hendrickx, Leo; Valk, Jody
Highlights: Chronic abdominal pain after laparoscopic Roux en Y gastric bypass (LRYGP) is a challenging clinical problem. An unusual case of a fish bone perforation at the biliary-digestive junction with resulting adhesions and obstruction is described. The importance of exercising a low threshold for laparoscopic evaluation in patients presenting with chronic abdominal pain after LRYGP is stressed. Abstract: Background: The management of chronic abdominal pain after laparoscopic Roux-en-Y gastric bypass (LRYGP) is complex and challenging. Foreign body intestinal perforation including that caused by fish bones has previously been reported in the literature and if clinically unrecognized, can cause significant morbidity and mortality. Fish bone perforation as a cause of chronic abdominal pain after LRYGP has rarely been reported. Summary: The unusual case of a 54 year old female presenting with recurrent episodes of postprandial pain 2 years after LRYGP is reported. Previous radiological and endoscopic investigations did not reveal any abnormality and after the most recent clinical presentation, a laparoscopic exploration was performed. A protruding fish bone at the biliary-digestive junction was discovered intra-operatively and successfully extracted. Dense adhesions between the involved intestinal loops were lysed in an attempt to improve intestinal transit and subsequently relieve post-prandial pain. Conclusion: This case highlights the possibility of a missed fish bone perforation causing chronic postprandial abdominal pain and discomfort in a patient with a Roux-en-Y gastric bypass anatomy. Foreign body perforation is a rare cause of abdominal pain after gastric bypass that should be considered when evaluating chronic abdominal pain symptoms after LRYGP.